A facile hydrothermal synthesis of visible-light responsive BiFeWO6/MoS2 composite as superior photocatalyst for degradation of organic pollutants. Issue 15 (15th October 2019) - Senthil, Raja Arumugam; Osman, Sedahmed; Pan, Junqing; Sun, Yanzhi; Kumar, T. Rajesh; Manikandan, A.
Abstract: In the present study, we have fabricated a new Z-scheme BiFeWO6 /MoS2 composite for photocatalytic elimination of organic contaminants from the waste-water. A series of BiFeWO6 /MoS2 composites were obtained by changing the amounts of BiFeWO6 from 1 to 10 mg through a facile hydrothermal method. The phase structures and morphologies of these BiFeWO6 /MoS2 composites were analyzed by SEM, HR-TEM, XRD, UV–vis DRS, element mapping and XPS techniques. Afterward, the dye-degradation experiments were conducted for the removal of Rhodamine B (RhB) using as-obtained BiFeWO6 /MoS2 composite samples under visible-light illumination to evaluate their photocatalytic activity. It is found that the BiFeWO6 /MoS2 composites exhibited great photocatalytic behavior than the pure BiFeWO6 and MoS2 samples. In particular, the BiFeWO6 /MoS2 composite with 5 mg of BiFeWO6 showed a quickly complete photocatalyst degradation ability of RhB in 75 min with high photo-stability and reusability behavior. This superior catalytic response of BiFeWO6 /MoS2 composite may be contributed by its high light harvesting capacity as well as fast separation and movement of photo-generated electron-hole pairs. This proposed BiFeWO6 /MoS2 composite is a very promising photocatalyst for environmental remediation work.